A Second Order Modified Characteristics Variational Multiscale Finite Element Method for Time-Dependent Navier-Stokes Problems (Journal of Computational Mathematics, 2018)
In this paper, by combining the second order characteristics time discretization with the variational multiscale finite element method in space we get a second order modified characteristics variational multiscale finite element method for the time dependent Navier-Stokes problem. The theoretical analysis shows that the proposed method has a good convergence property. To show the efficiency of the proposed finite element method, we first present some numerical results for analytical solution problems. We then give some numerical results for the lid-driven cavity flow with $Re$=5000, 7500 and 10000. We present the numerical results as the time is sufficiently long, so that the steady state numerical solutions can be obtained.
Keywords: Modified method of characteristics; Defect-correction finite element method; Navier-Stokes problems; Characteristics-based method; Lid-driven problem.